Новый род и вид жуков-щелкунов (Coleoptera, Elateridae) из Ирана - Гурьева, Е.Л. (Вестник зоологии, 1983)
A new genus Tolphoréa gen. n. is established with type-species Tolphorea volans sp. n. by original designation and monotypy. Described species is similar to Adrastus Esch. species, differs by structures of the front, prosternal sutures, mesosternal groove and metacoxal plates. Type-material: holotypé female, S.-W. Iran, Zagros Mis, Dasht-e Arzhan, 22.10. 1977, Gurjeva leg.; four female paratypes. Holotype and one paratype are deposited in the Zoological Institute, USSR Academy of Sciences (Leningrad), the rest — in the National Museum in Prague (Czechoslovakia).